The effects of global migration of male children on left-behind parents’ family and social life: The case of Pakistan - Asia Ashfaq (Faculty of Social and Political Science, Universitas Airlangga, 2020)
As a human phenomenon, international migration has been affecting societies politically, economically, and socially for a more extended period. The present study tried to investigate the trends of international migration and their effects on the social life of the elderly parents left behind by their children, who at this age need love, care, support, and time from their children. The study adopted a quantitative research design by surveying three cities: Pakistan and Azad Jammu and Kashmir, chosen based on many international migration trends in these regions. A sample of 94 respondents drawn using a snowball sampling technique. The results were gathered through a questionnaire and analyzed statistically. The results show that most parents reported that their social contacts have changed in their children's presence as they get busy with their children. The study finds international migration as affecting the social life (Activities of Daily Life or ADL) of elderly parents. Moreover, many respondents stated that their relatives’ attitude was amiable, caring, and respectable in their children's absence. Lastly, a more significant number of respondents agreed that their food and sleep habit changed to tremendous and some extent in their kids’ presence. This research concludes that parents need support from their kids and assume themselves as dependents in their aging stage.